The Paradox of Police Data - Wood, Stacy (KULA)

(untitled) (University of Victoria Libraries, 2018)
This paper considers the history and politics of ‘police data.’ Police data, I contend, is a category of endangered data reliant on voluntary and inconsistent reporting by law enforcement agencies; it is also inconsistently described and routinely housed in systems that were not designed with long-term strategies for data preservation, curation or management in mind. Moreover, whereas US law enforcement agencies have, for over a century, produced and published a great deal of data about crime, data about the ways in which police officers spend their time and make decisions about resources—as well as information about patterns of individual officer behavior, use of force, and in-custody deaths—is difficult to find. This presents a paradoxical situation wherein vast stores of extant data are completely inaccessible to the public. This paradoxical state is not new, but the continuation of a long history co-constituted by technologies, epistemologies and context.